The Roundtable on Sustainable Palm Oil (RSPO) and transnational hybrid governance in Ecuador's palm oil industry. (January 2022) - Johnson, Adrienne
Highlights: The local institutionalization of RSPO standards shifts national and sub-national structures of environmental governance, power, and authority. In Ecuador, palm oil governance is increasingly driven by a transnational regime of private and public institutions of governance. The state has pursued an alternative model of governance that harmonizes private regulatory instruments with national economic plans. Standards entrenchment has influenced community-company dynamics, public–private governing coalitions, and scalar approaches to landscape governance. New arrangements bring about novel governance coalitions and approaches while reinscribing the exclusionary nature of palm oil governance. Abstract: The expansion of Latin America's palm oil frontier has spurred an explosion of interest in the social and environmental impacts of palm oil production. Researchers have been particularly focused on the effectiveness of global sustainability certification standards in addressing induced vulnerabilities. Only a small fraction of this research, however, analyzes how the local institutionalization of global standards has shaped national and sub-national structures of environmental governance, or regional conceptualizations of authority. It also fails to examine how the entrenchment of global standards has reworked local social relations inhering within formal and informal palm oil governing arrangements. To address these gaps, this paper draws on the case of the Roundtable on Sustainable Palm Oil (RSPO) in Ecuador to answer the following research questions: 1) How does the local introduction and institutionalization of RSPO standards (re)shape national and sub-national environmental governance structures and relations? 2) How do RSPO standards reconfigure long-standing notions of power and authority? Drawing on extended fieldwork, the paper finds that the introduction of RSPO standards has prompted three major shifts in domestic palm oil governance. These shifts are: 1) technicalization of community-company relations, 2) hybridization of governance coalitions 3) regionalization of governance efforts. Taken together, these transformations point to an emerging transnational hybrid governance regime that blends public laws with private guidelines to reach national and international sustainability objectives. The regime has enabled the emergence of new palm governance authorities in the sector yet at the same time, it has reinscribed the uneven power relations of palm oil governance. The study concludes that future research and policy efforts must go beyond simply evaluating RSPO standards in local spaces, and instead aim to improve the social relations that exist within agro-commodity chains in order to make the governance of sustainable palm oil more socially-inclusive and just.